PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI MAN 3 KOTA PADANG - Hamidi, Zahid (Departemen Matematika, 2025)
In mathematics learning, learning outcomes have an important role in determining learning success. However, in reality, the mathematics learning outcomes of students in class XI MAN 3 Padang City still look low. One of the main causes is that students are still passive in the learning process. To overcome this problem, the Contextual Teaching and Learning (CTL) teaching model is used. This research aims to evaluate whether the mathematics learning outcomes of students in class XI MAN 3 Padang City using the CTL model are better than using conventional learning methods. This research uses a quasi-experiment design with Static Group Design. The population of this study were students of class The research instrument used was a mathematics learning outcomes test in the form of essay questions. Data analysis was carried out using the t-test. The results of the analysis show that the P-value is 0.000 in the t-test with a significance level (α) = 0.05. Because the P-value < α, it can be concluded that students who use CTL produce significant increases in learning outcomes compared to students who use conventional learning in class XI MAN 3 Padang City.Keyword - CTL Learning Model, Conventional Learning Model, Mathematics Learning